DJS as “populist” theologian – On Dirkie Smit’s newspaper column - Brand, Gerrit (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Dirkie Smit’s weekly newspaper column, written under the pseudonym DJS, is understood as constituting an important part of his academic theological literature. One of the characteristic theological perspectives found in these columns is the problematizing of any clear distinction between “church theology” and “public theology”. A further typical element of these columns is that forms of interpretation in which both “points of departure” as well as “hermeneutical horizons” appear, but these do not function in any contrasting way. Amazement and hope are themes often found in the columns. The column’s inherited title, “Geestelike Waardes” [Spiritual Values], can even be interpreted in those written by Smit as referring to the often-made distinction between “spiritual” and world in the ways he breaks through this distinction. Finally, the contrast of “public” and “popularistic” is analysed with reference to these columns.